Legal Awareness of Maduresse Nahdliyin: A Partnership Study between BMT Nuansa Umat and MWC NU - Rudy Haryanto (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2019)
Abstract:Building people’s legal awareness in various sectors, such as in the economic one, requires appropriate steps and strategies. This study examines the importance of partnership in building legal awareness on the aspect of Moslem’s economic sector. It captures a successful partnership pattern between BMT Nuansa Umat East Java and MWC NU in developing legal awareness specifically among nahdliyin. The study used descriptive qualitative method while its data collection techniques include observation, interviews and documentation. Respondents in this study consists of leaders of KSPPS BMT NU East Java and the Head of MWC NU. Based on the analysis of this research, it is clear that the type of business partnership between KSPPS BMT NU East Java and MWC NU is a partnership called by syirkah. This model is found to successfully achieve cultural, professional and mutual legal awareness.Keywords:Legal Awareness, Partnership, KSPPS BMT Nuansa Umat, MWC NU Abstrak:Membangun kesadaran hukum ummat dalam berbagai sektor, seperti pada sektor ekonomi, membutuhkan langkah dan strategi yang tepat. Penelitian ini mengurai pentingnya kemitraan dalam membangun kesadaran hukum pada bidang ekonomi umat Islam. Secara khusus, ia memotret keberhasilan pola kemitraan antara BMT Nuansa Umat Jawa Timur dengan MWC NU dalam mengembangkan kesadaran hukum khususnya di kalangan warga nahdliyin. Penelitian ini menggunakan metode deskriptif kualitatif. Teknik pengumpulan data meliputi observasi, wawancara dan dokumentasi. Responden dalam penelitian ini terdiri dari pimpinan KSPPS BMT NU Jawa Timur dan Ketua MWC NU. Berdasarkan analisis dan pembahasan dari hasil penelitian yang telahdiuraikan, dapat ditarik kesimpulan bahwa jenis kemitraan usaha yang dijalankan antara KSPPS BMT NU Jawa Timur dengan MWC NU adalah persekutuan (syirkah). Dalam kemitraan model ini, kesadaran hukum yang berbasis kultural, professional, dan kesalingan dapat tercapai.Kata Kunci: Kesadaran Hukum, Kemitraan, KSPPS BMT Nuansa Umat, MWC NU